Effect of wheat pearling process on composition and nutritional profile of flour and its bread-making performance - Navarro, José Luis (2021)
Pearling process on wheat grains was evaluated as a strategy to reduce their adverse effect on whole-wheat bread (WWB) quality and simultaneously preserve part of the nutrients of the whole grain. The grains were pearled applying different times (25, 125, 225 and 250 s) before milling. Characteristic, nutritional composition and rheology of the pearled wheat flour (P), and their bread-making performance, were analysed. Whole-wheat flour and refined flour (RF) were used as control. P125s, P225s and P250s exhibited a superior nutritional profile concerning RF. P had lower water absorption and led to higher volume bread with lighter crust and crumb compared to WWB. P125s, P225s and P250s bread showed characteristics similar to those of white bread, but their hardness was lower. The improvement resulted from the extraction of the outermost bran layers, a decrease in insoluble dietary fibre, an increase in the proportion of water-soluble pentosans and a lower protein weakening.